Formation and characterization of chitosan-based polyelectrolyte complex containing antifungal phenylpropanoids - Olea, Andrés F.; Carrasco, Héctor; Santana, Franco; Navarro, Laura; Guajardo Maturana, Raúl.; Linares Flores, Cristian Antonio. (MDPI, 2024)
In this work, a novel chitosan-based polyelectrolyte complex (PEC) was prepared using chitosan as the cationic polyelectrolyte, while a potassium salt of poly(maleic anhydride-alt-tetradecene) (PMA-14) served as the anionic counterpart. These PECs were used for the encapsulation of two nitroeugenol derivatives: 4-allyl-2-methoxy-6-nitrophenol (3) and 2-allyl-6-nitrophenol (4). The results confirm complex formation and efficient encapsulation of active compounds. Encapsulation efficiency (EE) was influenced by the chemical structure of the compounds, with 32.18% EE for 3 and 20.36% EE for 4. The resulting systems were characterized by fluorescence probing techniques, dynamic light scattering (DLS), and zeta potential. On the other hand, antifungal assays revealed that, in free form, 3 exhibits a much higher activity against Botritys cinerea than 4. However, no effect of encapsulation of both compounds on antifungal performance was observed. Results from molecular dynamic studies indicate that a stabilization effect is induced by compounds 3 and 4 during PEC formation, which is attributed to specific interactions between polyelectrolytes and guest molecules. These results are in line with the EE values measured for 3 and 4 and explain the low release from PECs of these molecules. Thus, the potential development of PEC-based systems for the delivery of bioactive compounds requires a deeper comprehension of parameters determining the relationship between encapsulation efficiency and delivery kinetics.
Keywords: Active compounds; Anhydride maleic derivative; Encapsulation; Quitosana; Anhídrido maleico